Plasma and Magnetic-Field Structure of the Solar Wind at Inertial-Range Scale Sizes Discerned From Statistical Examinations of the Time-Series Measurements - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2020)
This paper reviews the properties of the magnetic and plasma structure of the solar wind in the inertial range of spatial scales (500 - 5x106 km), corresponding to spacecraft timescales from 1 s to a few hr. Spacecraft data sets at 1 AU have been statistically analyzed to determine the structure properties. The magnetic structure of the solar wind often has a flux-tube texture, with the magnetic flux tube walls being strong current sheets and the field orientation varying strongly from tube to tube. The magnetic tubes also exhibit distinct plasma properties (e.g. number density, specific entropy), with variations in those properties from tube to tube. The ion composition also varies from tube to tube, as does the value of the electron heat flux. When the solar wind is Alfvénic, the magnetic structure of the solar wind moves outward from the Sun faster than the proton plasma does. In the reference frame moving outward with the structure, there are distinct field-aligned plasma flows within each flux tube. In the frame moving with the magnetic structure the velocity component perpendicular to the field is approximately zero; this indicates that there is little or no evolution of the magnetic structure as it moves outward from the Sun. Large sudden velocity shears are seen across the boundaries between the magnetic flux tubes as the magnetic field rotates and the field-aligned flow rotates. The effect of the solar-wind current sheets on the magnetic power spectral density of the solar wind is examined: the current sheets are found to dominate the spectral properties of the solar wind.